Pengukuran produktivitas lini produksi gula rafinasi dengan pendekatan Objective Matrix (OMAX) - Supriyadi Supriyadi; Andi Darmawan Suryadiredja (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
Productivity measurement has an important role in evaluating and establishing the next strategy in increasing productivity levels. This study aims to determine the level of productivity of a refined sugar company and provide suggestions for improvements to increase the level of productivity. This research uses the Objective Matrix (OMAX) method with five ratio indicators, namely yield achievement, actual production achievement criteria, boiler natural gas consumption criteria, electricity consumption criteria, and employee absenteeism criteria. This study uses company data for 2018 in accordance with company recommendations. The results showed that for one year, the productivity values and performance index differed each month. The performance index with the highest point was in February, which reached 426.3% and in May, which reached 306%. Based on the traffic light system, ratio 1 has six minimum performance periods, ratio 2 has eight minimum performance periods, ratio 3 has four minimum performance periods, ratio 4 has four minimum work periods, and ratio 5 has five minimum work periods. Improvement steps that can be done to improve the actual achievement of production are the provision of regular training to enhance skills and cooperation between operators, improvement of maintenance management systems, development of air circulation, and supplier evaluation. The OMAX method can identify performances that have below standard production, and recommendations for improvement can be prioritized on the ratio that experiences the most substandard performance.